Online learning platform during Covid-19 pandemic: An exploratory factor analysis on students’ attitude and perceived usefulness in media and communication education - Hasmah Zanuddin; Nursyamira Shaid; Zulfadhli Halim (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
Due to Covid-19 and Movement Control Order (MCO) policy, Malaysian Higher Learning institution has decided to shift the learning into online learning mode. In this research, we examined the readiness and attitude of the Media and Communication undergraduate students for online learning platform during pandemic. A total of 144 studentsâ€™ responses and Technology Acceptance Model (TAM) were used as theoretical framework. Research data were analyzed using SPSS and exploratory factor analysis (EFA) was utilised to extract the prominent factors. Component based examined using eigenvalue, scree plot and rotation was done by varimax method. The items with 0.5 loading or greater were considered significant. The findings showed that Perceived Usefulness was determined by two significant indicators, i.e. enhancing effectiveness in learning and improving learning performance with factor loadings; .869 and .849 consecutively. Attitude factor loading, meanwhile, showed that two indicators played a dominant role; using online learning is a bad idea throughout the coursework and positive attitude towards online learning and usefulness towards study; .762 and .816. The attitude of the students displayed unhappiness using the online learning platform for the entire semester due to the limitation of face-to-face (F2F) lab classes such as studio-based learning. However, the students had no problem in understanding the online platform utilized.Â